2003
DOI: 10.1523/jneurosci.23-12-04931.2003
|View full text |Cite
|
Sign up to set email alerts
|

Experiments to Test the Role of Phosphatidylinositol 4,5-Bisphosphate in Neurotransmitter-Induced M-Channel Closure in Bullfrog Sympathetic Neurons

Abstract: Various neurotransmitters excite neurons by suppressing a ubiquitous, voltage-dependent, noninactivating K+ conductance called the M-conductance (gM). In bullfrog sympathetic ganglion neurons the suppression of gM by the P2Y agonist ATP involves phospholipase C (PLC). The present results are consistent with the involvement of the lipid and inositol phosphate cycles in the effects of both P2Y and muscarinic cholinergic agonists on gM. Impairment of resynthesis of phosphatidylinositol 4,5-bisphosphate (PIP2) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 45 publications
5
63
0
Order By: Relevance
“…First, inhibiting the formation of phosphatidic acid does not bother suppression or recovery. A similar result with R59022 was obtained in bullfrog [24]. Second, all products of DAG metabolism (such as arachidonic acid) must be produced slowly, as DAG is normally metabolized with a time constant of 80 s. This would mean that these products are not generated significantly during the onset of inhibition (<7 s) and start to accumulate only during the recovery phase for short agonist exposures.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…First, inhibiting the formation of phosphatidic acid does not bother suppression or recovery. A similar result with R59022 was obtained in bullfrog [24]. Second, all products of DAG metabolism (such as arachidonic acid) must be produced slowly, as DAG is normally metabolized with a time constant of 80 s. This would mean that these products are not generated significantly during the onset of inhibition (<7 s) and start to accumulate only during the recovery phase for short agonist exposures.…”
Section: Discussionsupporting
confidence: 72%
“…Our point is that such actions would have to be slow to develop after application of a stimulus for PLC. Ford et al [24] did find that if DAG kinase was inhibited with R59022, repeated PLC activation eventually slowed recovery of M current, presumably reflecting the stoppage of phosphatidylinositol regeneration from phosphatidic acid. The possibility of roles for PKC remains a more difficult question.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of G-protein-coupled receptors of the Gq/11 family strongly suppresses M-channels (Delmas and Brown, 2005), via depletion of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) upon muscarinic receptor stimulation (Suh and Hille, 2002;Ford et al, 2003;Zhang et al, 2003;Suh et al, 2004;Winks et al, 2005) or via Ca 2ϩ -calmodulin (CaM) action on the channels upon bradykinin B 2 and purinergic P 2 Y receptor activation (Cruzblanca et al, 1998;Bofill-Cardona et al, 2000;Gamper and Shapiro, 2003;Zaika et al, 2007). Recently, syntaxin 1A (Syx), a plasma membrane protein component of the exocytotic SNARE complex, shown to interact physically and functionally with different voltage-gated K ϩ channels (Fili et al, 2001;Leung et al, 2003Leung et al, , 2007Michaelevski et al, 2003Michaelevski et al, , 2007Tsuk et al, 2005;Yamakawa et al, 2007;Regev et al, 2009), was suggested to be another blocker of M-channels (Regev et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In bullfrogs, there are three distinct GnRH receptor subtypes, all of which appear capable of coupling to G q (Wang et al 2001). Within the sympathetic ganglia, LHRH activates PLC to increase inositol trisphosphate turnover and intracellular Ca 2ϩ concentration (Pfaffinger et al 1988) and to suppress M-type K ϩ current (Ford et al 2003b(Ford et al , 2004, suggesting that the LHRH/GnRH receptor(s) in this tissue is/are also coupled to G q/11 . It is yet to be determined which of the three identified bullfrog GnRH receptors is/are involved in both this process and the neurotrophic effects described in the present work.…”
Section: Role Of G-proteins and Protein Kinases In The Effect Of Lhrhmentioning
confidence: 99%
“…The present experiments were therefore undertaken to determine 1) whether LHRH-induced increase of I Ca in BFSG proceeds via the MAPK pathway in a similar fashion to NGF, 2) how Gprotein-coupled LHRH receptors signal to the MAPK pathway, 3) the mechanism whereby NGF produces long-term increases in I Na , and 4) whether LHRH has access to this transduction mechanisms so that it can produce long-term increases in I Na in the same way as NGF. Parts of this work were published in preliminary reports (Ford and Smith 2000;Lu et al 2002;Wong et al 2006).…”
Section: Introductionmentioning
confidence: 98%